Introducing scientific argumentation practices in physics teacher's undergraduate curricula - Figueira, M. J.S. [UNESP]; Nardi, R. [UNESP]; Cortela, B. S.C. [UNESP] (IOP Publishing, 2019)
Recent educational research has suggested that introducing argumentation practices in science classrooms is an important approach to reach the goals of SSI education. However, it is safe to state that few undergraduate students have had the chance to engage in such practices during their time of formal instruction. With this in mind, this paper aims to present a case study about the introduction of argumentation practices that has been carried out with the participation of seven undergraduate Physics students of a public university in the state of Sao Paulo, Brazil. The debate was conducted as a simulated public hearing session, in which students were grouped in pairs and each pair was called to interpret a different social group involved in the Brazilian nuclear plan issue. The analysis was done using a recent methodology developed especially for argumentation exchanges in classrooms. While mediating the debate session, it was possible to notice a deep immersion in the role-played characters and a wider understanding of the social, economic and political issues involved in the nuclear area of Brazil.